Hypoglycemia in Columba livia Due to the Infection of Apicomplexan Parasites - Ramesh Chandra2, Nasim Jahan1* and (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> ABSTRACT: The impact of two apicomplexan parasites, Haemoproteus and Plasmodium species in naturally infected Columba livia was evaluated in order to examine the effects on the host. Haemoproteus occurred at a higher prevalence (55.63%) in Columba livia as compared to Plasmodium (6.76%). Blood sugar level was found to be 273.27 ± 1.13 mg/dl and 269.25 ± 1.18 mg/dl in uninfected male and female C. livia respectively. In lone infection of Haemoproteus the values of glucose decreased by 16.37% in male and 18.17% in female pigeons. The values decreased by 21.27% and 21.99% in male and female pigeons respectively under concurrent infections of Haemoproteus and Plasmodium as compared to uninfected C. livia indicating that hypoglycemia is a frequent outcome of apicomplexan infection and that the manifestation is greater under concurrent infectivity. Key words: Glucose, Haemoproteus, Plasmodium, concomitant 1Department of Life Science, R.K.S. Degree College, Sahawar Kanshiramnagar 207245 (U.P.) India; 2S.S.(P.G.) College, Shahjahanpur, U.P. India